2014
DOI: 10.4018/978-1-4666-6162-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Information Capitalism and Globalization on Teaching and Learning

Abstract: Education is undergoing constant changes under the effects of globalization and information generation, processing, and transmission, which is termed "informational capitalism." The aims of this chapter are to explore how digital technologies have transformed the productive forces of capitalism and have enabled a globalized economy. The research design adopted for this study is the descriptive survey. The population for the study consists of students and faculty from Robert Morris University in Pennsylvania an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Hofstede's work is the inspiration behind this research, where the aim is to investigate possible correlations between ethnicity and personality type. Hofstede's work confirmed that people in different nations astoundingly had similar results when questioned about values [14]. Thus, he succeeded in dissecting the results and clustering them into groups of 'nations' and then placing these nations into one of the four quadrants he developed of 'perceived values'.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Hofstede's work is the inspiration behind this research, where the aim is to investigate possible correlations between ethnicity and personality type. Hofstede's work confirmed that people in different nations astoundingly had similar results when questioned about values [14]. Thus, he succeeded in dissecting the results and clustering them into groups of 'nations' and then placing these nations into one of the four quadrants he developed of 'perceived values'.…”
Section: Introductionmentioning
confidence: 84%
“…While North American and European countries can be regarded as largely individualistic, displaying high scores such as 80 for both Hungary and Canada, this cannot be said for Asian, African and Latin American countries. These exhibit clear collectivist beliefs, showing low scores, such as Colombia (13) and Indonesia (14). The degree of contrast that exists can be seen through an examination of two countries at opposing ends of the spectrum, with Guatemala scoring 6 and United States scoring 91.…”
Section: Cultural Variancesmentioning
confidence: 99%
“…In other words, the Theory is used to differentiate between the cultures of different races and examine cultural dimensions to assess their impact on a business environment. Hofstede's Theory demonstrates the influence of a society's culture on its members' values and indicates how these values are linked to behaviour (Adeoye & Tomei, 2014). Gray (1988) contends that Hofstede's (1980) cultural dimensions influence a country's accounting system in two ways: through their influence on a country's institutions, such as its capital markets, and through their influence on accounting values, such as conservatism, and earning management shared by members of a country's accounting subculture.…”
Section: Ceo Turnovermentioning
confidence: 99%